Determinants Related to User Perceptions of the Quality of Health Home Outpatient Services in DKI Jakarta After Rebranding in 2025 - Tri Narsih; Tri Suratmi; Laila Ulfa; Irwan Irwan (CV. Inara, 2025)
Healthcare service quality is a key indicator in evaluating the effectiveness of healthcare facilities, influencing patient satisfaction and loyalty. Understanding users' perceptions of service quality is essential for developing strategies to improve outpatient care. This study aims to analyze factors affecting users' perceptions of service quality at Rumah Sehat outpatient units in Jakarta in 2025. A quantitative survey design was employed, involving 96 purposively sampled respondents. The data were analyzed using the chi-square test to determine the relationship between demographic characteristics, payment methods, and users' perceptions of service quality. The results indicate that users' perceptions are significantly influenced by age, education, and payment methods, with payment method being the most dominant factor. Moreover, professional, friendly, and responsive healthcare staff, along with adequate and comfortable facilities, contribute to positive user perceptions. These findings provide practical implications for Rumah Sehat management to enhance service quality, patient satisfaction, and user loyalty.